Clinical and economic impacts of explicit tools detecting prescribing errors: A systematic review. (25th March 2021) - Farhat, Akram; Al‐Hajje, Amal; Csajka, Chantal; Panchaud, Alice
Abstract: What is known and objective: Many explicit tools have been developed to reduce prescribing errors and ensure patients' safety. The impact of explicit tools is not well studied. The objective of this study was (a) to conduct a systematic review of systematic reviews listing explicit tools developed to detect prescribing errors and (b) to assess their impact on clinical and economic outcomes. Methods: This project includes two related parts. First, a systematic review of systematic reviews listing explicit tools dedicated to geriatrics or internal medicine was performed to develop an exhaustive list of explicit tools. Then, using the list compiled in the first step, a systematic review of randomized controlled trials (RCT) assessing clinical or economic impacts of tools was performed to evaluate their usefulness. Results and discussion: The systematic review of systematic reviews identified 49 explicit tools. The systematic review of RCT, using one or more of the 49 explicit tools, identified 5 RCT using explicit tools as intervention (3 STOPP/START and 2 FORTA RCT). The 5 studies evaluated clinical impacts with 3 RCT identifying significant clinical impacts (falls, activities of daily living and/or adverse drug reactions) and 2 STOPP/START RCT identifying significant economic impacts. What is new and conclusion: The systematic review of RCT showed that explicit tools can have some effect in improving patients' safety. Further studies are warranted to better characterize their clinical and economic impact. Abstract : Very little is known regarding the clinical and economic impact of the prospective use of explicit tools detecting prescribing errors. We found a significant impact of STOPP/START on adverse drug reactions and medication costs and a significant impact of FORTA on falls, activities of daily living and adverse drug reactions. These findings suggest that explicit tools support reducing the complexity of therapeutic management and tools‐based interventions could have a usefulness in clinical practice.